1976
DOI: 10.1111/j.1752-0606.1976.tb00405.x
|View full text |Cite
|
Sign up to set email alerts
|

Marital Intimacy and the Deadly Love‐Anger Cycle

Abstract: The view is advanced that the fundamental cause of marital failure in our time is the inability to resolve the anger which is inevitably generated in an intimate relationship. The nature of anger, its impact on a love relationship, and its constructive management in marriage are examined. The concept of training couples in “marital fighting” is rejected in favor of a three‐step procedure which the author has tested out in his own marriage, and taught to other couples, with very satisfactory results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1977
1977
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…A body of evidence also indicates that unexpressed anger interferes with cognitive efficiency (Holt, 1970). Several clinically oriented theoreticians contend that unexpressed anger or misdirected hostility endangers interpersonal intimacy (Holt, 1970;L'Abate, 1977;Mace, 1976;Novaco, 1976a). Megargee (1966) has found some support for the contention that some aggressive persons may be chronically overcontrolled and that aggression by such persons is apt to be of "murderous intensity," since an aggressive impulse must build to higher levels to overcome inhibitions against aggressive expression.…”
mentioning
confidence: 99%
“…A body of evidence also indicates that unexpressed anger interferes with cognitive efficiency (Holt, 1970). Several clinically oriented theoreticians contend that unexpressed anger or misdirected hostility endangers interpersonal intimacy (Holt, 1970;L'Abate, 1977;Mace, 1976;Novaco, 1976a). Megargee (1966) has found some support for the contention that some aggressive persons may be chronically overcontrolled and that aggression by such persons is apt to be of "murderous intensity," since an aggressive impulse must build to higher levels to overcome inhibitions against aggressive expression.…”
mentioning
confidence: 99%
“…A common paradigm is the distinction between anger-in (suppressed or unexpressed anger), anger-out (displaced anger or hostility), and anger-discuss (optimal anger expression). The consequences of suppressed anger appear to be destructive, including suicide (Apter et al, 1989), impaired interpersonal relationships (Holt, 1970;Mace, 1976), heart disease (Haynes & Feinleib, 1980), and high blood pressure (Harburg et al, 1973), whereas anger-out has been associated with the use of projection and denial (Apter et al, 1989), increased aggression (Berkowitz, 1970), a greater number of health problems (E. H. Johnson & Broman, 1987), and depression (Maiuro, Cahn, Vitaliano, Wagner, & Zegree, 1988). Frazier (1995) suggested that anger expression, in and of itself, is not useful for the individual without the discovery of frustrations that lie behind it.…”
Section: Anger and Violencementioning
confidence: 99%
“…Although aggression may be a form of anger expression, it often represents the mismanagement of anger since it inhibits the goal of improving a relationship. Mace (1976) refers to aggressive anger as venting and states it may prove destructive in intimate relationships. Venting includes acts of physical and verbal aggression aimed at attack, insult, or blame.…”
Section: Anger Management Principle #4: Developing Empathy Skills Andmentioning
confidence: 99%
“…Venting includes acts of physical and verbal aggression aimed at attack, insult, or blame. These expressions may also involve distorted, indirect, contradictory, or dishonest communication (Mace, 1976). Baldwin (1983) indicates that when anger serves as a means of overpowering or hurting rather than as a method of communication, it is not being handled effectively.…”
Section: Anger Management Principle #4: Developing Empathy Skills Andmentioning
confidence: 99%
See 1 more Smart Citation